Voxel based analysis of recurrence dynamics in intracranial aneurysms after coiling - Ernst, Marielle Sophie Katherine; Möhlenbruch, Markus Alfred; Bendszus, Martin (Journal of neuroInterventional surgery, 2018)
Background: Understanding aneurysm growth is critical for the appropriate follow-up of patients after coil embolization and the need for retreatment. The purpose of the study was to stratify the growth dynamics of aneurysm recurrences after coiling by volumetric analysis and to determine predictive factors for aneurysm recurrences. - Methods: Source images of follow-up three-dimensional time of flight MR angiography (ToF-MRA) scans were compared with the first post-interventional ToF-MRA scan and analyzed for residual flow after co-registration using ANALYZE-software. In the event of incomplete occlusion, the residual volume was segmented and calculated. Growth dynamic was determined for each aneurysm after embolization. - Results: We analyzed 326 patients with 345 aneurysms from two centers. Each case had at least two ToF-MRA examinations after endovascular therapy. The mean observation interval was 59 months. Volumetric analysis of 1139 follow-up MRAs revealed that 218/345 aneurysms (63.2%) showed complete occlusion on initial follow-up imaging, and of these 95.0% remained stable. A steady increase in intra-aneurysmal flow was observed in 83/345 (24.1%). Less frequent observations were a steep increase (21/345; 6.1%) and a decrease (27/345; 7.8%). Independent predictors of increasing residual flow were greatest aneurysm diameter, total coil length, and incomplete occlusion. - Conclusions: Volumetric analysis of registered three-dimensional ToF-MRA follow-up datasets allows the detection of different growth patterns with high precision, avoids the low inter-rater reliability, and represents a promising approach for future studies that include analysis of more complex predictors of residual flow. In cases of aneurysm recurrence after coiling, the major pattern seems to be a steady increase in intra-aneurysmal flow over several months.
Gesehen am 22.11.2018
Published online first: 31 October 2017